Defects evolution of nanoporous AuAg(Pt) during thermal coarsening. (1st July 2016) - Gao, Panpan; Ye, Xinglong; Zhu, Zhejie; Wu, Yichu; Volinsky, Alex A.; Qiao, Lijie; Su, Yanjing
Abstract: Vacancies and voids evolution within the nanoporous (np) AuAg(Pt) ligaments during thermal coarsening was investigated by positron annihilation spectroscopy and scanning electron microscopy (SEM). Partially dealloyed ternary np AuAg(Pt) samples with 5–8 nm ligaments were prepared by electrochemical dealloying of (Au0.95 Pt0.05 )25 Ag75 ingots. Positron lifetime experiments demonstrated that nano-ligaments are stable against coarsening below 320 °C. Vacancies play an essential role during the coarsening process. Lifetime parameters changed above 320 °C, associated with a large number of vacancies and divacancies formed via coarsening with large enclosed voids formed at the same time. SEM images demonstrate ligaments growing non-uniformly during thermal coarsening. Graphical abstract: Microstructure evolution of the np Au(Pt) annealed at various temperatures for 30 min.